Organic Solar Cell With Efficiency Over 20% and VOC Exceeding 2.1 V Enabled by Tandem With All‐Inorganic Perovskite and Thermal Annealing‐Free Process - Xiaoyu Gu; Xue Lai; Yuniu Zhang; Teng Wang; Wen Liang Tan; Christopher R. McNeill; Qian Liu; Prashant Sonar; Feng He; Wenhui Li; Chengwei Shan; Aung Ko Ko Kyaw (Advanced Science, 2022)
Abstract Organic solar cells (OSCs) based on polymer donor and non‐fullerene acceptor achieve power conversion efficiency (PCE) more than 19% but their poor absorption below 550 nm restricts the harvesting of high‐energy photons. In contrast, wide bandgap all‐inorganic perovskites limit the absorption of low‐energy photons and cause serious below bandgap loss. Therefore, a 2‐terminal (2T) monolithic perovskite/organic tandem solar cell (TSC) incorporating wide bandgap CsPbI2Br is demonstrated as front cell absorber and organic PM6:Y6 blend as rear cell absorber, to extend the absorption of OSCs into high‐energy photon region. The perovskite sub‐cell, featuring a sol–gel prepared ZnO/SnO2 bilayer electron transporting layer, renders a high open‐circuit voltage (VOC). The VOC is further enhanced by employing thermal annealing (TA)‐free process in the fabrication of rear sub‐cell, demonstrating a record high VOC of 2.116 V. The TA‐free Ag/PFN‐Br interface in organic sub‐cell facilitates charge transport and restrains nonradiative recombination. Consequently, a remarkable PCE of 20.6% is achieved in monolithic 2T‐TSCs configuration, which is higher than that of both reported single junction and tandem OSCs, demonstrating that tandem with wide bandgap all‐inorganic perovskite is a promising strategy to improve the efficiency of OSCs.